Sphalerite and Pyrite on Kuroko-Type Ore Deposit: A Case Study of Phase Ambiguity and Its Prediction Technique by Means of X-Ray Diffraction Analysis - Ibrahim Purwariadi (Jurnal Geologi dan Sumberdaya Mineral, 2020)
Kuroko-type VMS (volcanogenic massive sulfide) ore deposit is a deposit that has some abundant sulfide minerals such as pyrite, chalcopyrite, galena and sphalerite. Besides them, other common sulfide minerals also occur, such as bornite, acanthite (argentite) and some of tennantite-tetrahedrite series. In some cases, we can find sphalerite and pyrite on these deposits. These cases often make the difficulty of XRD analysis. It is caused by some overlapping diffraction peaks between pyrite and sphalerite, which are difficult to be distinguished. This problem can cause miscalculation of weight fraction between them. Therefore, this study was done in order to make sure the true phase between pyrite and sphalerite of the overlapping diffraction peaks. Cubic structure analysis and precise lattice parameter calculation were used as the method in this study in order to determine the true phase of sphalerite-pyrite overlapping peaks. An XRD analysis on the case study sample shows that there are five cubic planes, i.e. (111), (200), (220), (113), and (222) on some overlap diffraction peaks. By utilizing this method, these cubic planes can be distinguished where (111) and (113) are pyrite phases while (200), (220) and (222) are sphalerite phases.Keywords: Kuroko, sphalerite, pyrite, XRD, precise lattice parameter.